AMPHIPOD DISTRIBUTION IN THE SOFT-BOTTOM SUBTIDAL ZONES OF JAVA ISLAND IN RELATION TO SEDIMENT TYPES - Arfianti, Tri; Sihaloho, Hendra F.; Purbonegoro, Triyoni; Suratno, -; Arifin, Zainal (Marine Research in Indonesia, 2015)
Amphipods inhabit many marine benthic habitats and have an important ecological role. However, there is a lack of information about Indonesian amphipod diversity and distribution, especially in the shallow subtidal sediments of Probolinggo and Tangerang. During the transition to the monsoon season in September 2014, eight subtidal stations were sampled in Bayeman (Probolinggo) on East Java and seven subtidal stations were sampled in Kramat Kebo (Tangerang) in West Java. A total of 7346 amphipods individuals were collected, comprising five genera. Genus Photis was the most abundant group, followed by Grandidierella and Synchelidium. Multivariate analyses of these data indicated that sampling location and sediment granulometry were major determinants of distribution and composition of amphipods in Probolinggo and Tangerang.